Reflective arrayed waveguide grating with parallel arms using one‐dimensional photonic crystal reflector. Issue 21 (1st October 2019) - Okayama, H.; Onawa, Y.; Takahashi, H.; Shimura, D.; Yaegashi, H.; Sasaki, H.
Abstract : The authors demonstrate reflective arrayed waveguide grating designed for silicon waveguide. The phase shift sections of the arrayed waveguide are placed in parallel configuration. This enables the construction of compact device. The one‐dimensional photonic crystal is used as the reflector at the end of the arm. Wide reflection bandwidth is obtained.